Response Mixture Modeling of Intraindividual Differences in Responses and Response Times to the Hungarian WISC-IV Block Design Test - Molenaar, Dylan; Bolsinova, Maria; Rozsa, Sandor; De Boeck, Paul (Journal of intelligence, 2016)
Response times may constitute an important additional source of information about cognitive ability as it enables to distinguishing between different intraindividual response processes. In this paper, we present a method to disentangle interindividual variation from intraindividual variation in the responses and response times of 978 subjects to the 14 items of the Hungarian WISC-IV Block Design test. It is found that faster and slower responses differ in their measurement properties suggesting that there are intraindivual differences in the response processes adopted by the subjects.